The protective role of caffeic acid on bovine mammary epithelial cells and the inhibition of growth and biofilm formation of Gram-negative bacteria isolated from clinical mastitis milk - Xu, Tianle; Zhu, Hao; Liu, Run; Wu, Xinyue; Chang, Guangjun; Yang, Yi; Yang, Zhangping (Frontiers in Immunology, 2022)
As a first-line barrier against the bacterial infection of mammary tissues, bovine mammary epithelial cells (bMEC) are generally believed to be involved in the immune response due to exogenous stress. Due to the escalating crisis of antibiotic resistance, there is an urgent need for new strategies to combat pathogenic bacteria-infected bovine mastitis. In this study, isolated bMEC and ICR mice were used for E. coli infection and caffeic acid (CA) pretreatment experiments in vitro and in vivo. The inhibitory effect of CA on the bacterial growth and biofilm formation were also performed with bacteria strains isolated from mastitis infected milk. it was demonstrated that CA supplementation prohibits the growth of the predominant strains of bacteria isolated from clinical bovine mastitis milk samples. CA was found to disrupt the biofilm formation of E. coli B1 in a sub-MIC and inhibited the adherence property of E. coli on bMECs by decreasing the staining of bacteria on cell surfaces in vitro. In addition, CA was found to attenuate proinflammatory and oxidative responses in cells infected with E. coli. The pretreatment of bMECs with CA also restored altered lipid homeostasis caused by E. coli stimulation. The protective role of CA was further confirmed via the administration of CA in mice followed by representative Gram-negative bacterial infection. Collectively, these findings highlight the potential of CA to mediate Gram-negative infections and indicate that it has the potential to be developed as a novel antibacterial drug.